Episodic bradycardia as neurocardiac prodrome to voltage-gated potassium channel complex/leucine-rich, glioma inactivated 1 antibody encephalitis. - Naasan, G; Irani, SR; Bettcher, B; Geschwind, MD; Gelfand, J (2014)
IMPORTANCE: Voltage-gated potassium channel complex antibody (VGKCc-Ab) encephalitis is an immunotherapy-responsive syndrome usually associated with causative antibodies that target the leucine-rich, glioma inactivated 1 (LGI1) protein. Although it is expressed throughout the brain, LGI1 is not known to be expressed in cardiac tissue. We describe a novel neurocardiac prodrome of VGKCc-Ab/LGI1-encephalitis. OBSERVATIONS: Among 14 patients with VGKCc/LGI1-Ab encephalitis evaluated in the University of California, San Francisco Autoimmune Encephalitis Clinic and Rapid Dementia Research Program, 3 patients (2 men and 1 woman; aged 53, 55, and 64 years) exhibited episodic bradycardia that preceded the onset of encephalopathy by approximately 2 months and was severe enough to lead to pacemaker implantation. Serum LGI1-Ab results were positive when tested at the time of the subsequent encephalopathy. All 3 patients developed hyponatremia; none had faciobrachial dystonic seizures or malignancy. Brain magnetic resonance imaging was abnormal in 2 cases. None of the patients experienced further symptomatic bradyarrythmias after 1.7 to 7 years of follow-up. CONCLUSIONS AND RELEVANCE: Episodic bradycardia is a distinctive neurocardiac prodrome of VGKCc/LGI1-Ab encephalitis. The neuroanatomical localization most likely relates to insular and temporal lobe involvement, cortical regions that modulate cardiac autonomic function. Further study is needed to determine if recognition of this neurocardiac prodrome and earlier institution of immunosuppression can prevent the development of encephalopathy.